TOPENG MERSAM 1940AN HINGGA SETELAH TAHUN 1990 AN - Robi Febriansyah (Universitas Batanghari Jambi, 2019)
AbstractThe existence of mersam masks as a product of culture and economic productsfrom the 1940s until after the 1990s, was intended to see the symbolic meaning of the Mersam Mask as part of the culture and philosophy of the procession procession in the marriage ceremony in Mersam. The existence of elements supporting Mersam Mask culture, ranging from traditional leaders, mask wearers, mask craftsmen, and Mersam residents who became spectators of the mask performances. Making the mask influence the economy of the Mersam community by becoming a mask craftsman.the existence of the Mersam Mask is in a fluctuating condition, from function to the time of the show. During the 1940s until after the 1990s there were changes in the function of masks in Mersam from Magico-religious to profane. Meanwhile, the mask show went down in 2009, and began to rise again in 2011. Keywords: Mersam Mask, Magico-Religious, Profane, Culture AbstrakKeberadaan topeng mersam sebagai produk budaya dan produk ekonomi periode1940an hingga setelah tahun 1990an, dimaksudkan untuk melihat makna simbolis dari Topeng Mersam sebagai bagian dari budaya beserta filsofis dari prosesi arak- arakkan dalam upacara perkawinan di Mersam. Adanya unsur-unsur pendukung kebudayaan Topeng Mersam, mulai dari pemuka adat, pemakai topeng, pengrajin topeng, dan Penduduk Mersam yang menjadi penonton pertunjukan topeng. Menjadikan topeng mempengaruhi ekonomi masyarakat Mersam dengan cara menjadi pengrajin topeng. keberadaan Topeng Mersam berada pada kondisi yang fluktuatif mulai dari fungsi, hingga waktu pertunjukannya. Selama periode1940an hingga setelah tahun 1990an terjadi perubahan-perubahan fungsi topeng di Mersam mulai dari Magico-religius menjadi profane.Sementara itu waktu pertunjukan topeng mengalami kemunduran tahun 2009, dan mulai bangkit kembali tahun 2011.Kata Kunci : Topeng Mersam, Magico-Religius, Profane, Kebudayaan